Effect of Red Bajakah Tampala Flavonoid Concentration as Antibacterial on Bacillus subtilis - Devika Khoirul Hafifah; Suparno Suparno (Jurnal Ilmiah Sains, 2023)
Red bajakah tampala (Spatholobus littoralis Hassk.) is one type of bajakah that the Dayak people use as traditional medicine. Red bajakah tampala roots contain chemical compounds, namely flavonoids, which have antibacterial activity. This study aims to determine the effect of flavonoid concentration of red bajakah tampala root extract on the inhibitory power of Bacillus subtilis bacteria and the length of survival time. Bajakah root extract is obtained by decoctation method. The flavonoid content contained in bajakah extract was determined using the visible spectrophotometric method. The particle size was determined by a particle size analyzer (PSA), and the inhibition was tested by the Kirby Bauer technique. In an effort to identify bajakah root extract, density, viscosity, and refractive index were measured. The test results using the visible spectrophotometric method showed that the sample had a flavonoid concentration of 16.28 ppm. Meanwhile, the PSA test results showed that the particle size of bajakah extract was 94.6 nm. The antibacterial test results showed that the diameter of the clear zone increased from (6.23 ± 0.03) mm to (7.18 ± 0.06) mm according to the increase in flavonoid concentration from 10 ppm to 30 ppm. The ability of bajakah extract to survive in inhibiting bacteria varied from 48 hours to 72 hours. The results of measurements of density, viscosity, and refractive index are (0,960  0,002) gram/cm3, (0,890  0,010) , dan 1,3350  0,0005 respectively. Keywords: Bacillus subtilis; decoctation; flavonoids; Red bajakah tampala